Karakteristik Fisik, Kimia dan Sensoris Roti Tawar dengan Substitusi Tepung Edamame dan Penambahan Gum Guar - Reyvaldi Yorky (Fakultas Teknologi Pertanian, 2026)
White bread is a food product widely consumed by the public because it is practical and easily obtained. The increasing consumption of bread encourages the development of bread products with improved nutritional value. One effort that can be made is by utilizing edamame flour as a substitution ingredient because it has high protein, fat, and fiber content. However, the use of non-gluten flour can reduce bread quality; therefore, additional ingredients such as guar gum are needed, which function as hydrocolloids to improve dough structure. This study aimed to determine the effect of edamame flour substitution and guar gum addition on the physical, chemical, and sensory characteristics of white bread and to determine the best formulation. This study used a Completely Randomized Design (CRD) with two factors: substitution of wheat flour with edamame flour (10%, 20%, and 30%) and guar gum concentration (2%, 3%, and 5%) with two replications. The observed parameters included physical analysis (expansion volume, hardness, and color), sensory analysis (color, aroma, taste, and texture), and chemical analysis (moisture content, ash content, fat content, protein content, and carbohydrate content) on the best treatment based on physical and sensory analyses. Data were analyzed using ANOVA (Analysis of Variance) in SPSS 24.0 followed by Duncan’s New Multiple Range Test (DMRT), and sensory data were analyzed using the Chi-square test. The results showed that edamame flour substitution and guar gum addition had a significant effect (α ≤ 0.05) on specific volume, hardness, color, and sensory properties of white bread. The best treatment was obtained from the combination of 20% edamame flour substitution and 3% guar gum addition (A2B2) with an effectiveness value of 0.99, producing a specific volume of 5.44 ml/g, hardness of 44.51 gf, and lightness (L*) of 76.1. The sensory scores of the best treatment were color 4.04 (like), aroma 3.84 (neutral), taste 3.88 (neutral), and texture 4.04 (like). Chemical analysis of the best treatment showed moisture content of 39.42%, ash content of 1.16%, fat content of 4.04%, protein content of 15.30%, and carbohydrate content of 40.08%.
FINALISASI oleh Arif 2026 Juni 23
Keywords: white bread; edamamame; flour; guargum